The monk who sold his Ferrari : a spiritual fable about fulfilling your dreams and reaching your destiny - Sharma, Robin S. (Robin Shilp), 1964- (Harper Thorsons, 2014)
Advice on life strategies presented through a fictional account of what an ex-lawyer learned from Himalayan gurus.